Operating Environment Assessment of the Coalface in Underground Coal Mining Based on Analytic Hierarchy Process (AHP) and Matter-Element Theory (MET). (2nd August 2021) - He, Jianghui; Liu, Shiliang; Li, Wenping; Qiao, Wei; Yang, Zhi; Wang, Qiqing
Abstract : The environmental evaluation of the coalface in underground mining is of great significance to the safety of production and the health of miners. In order to achieve the objective and accurate evaluation of the operating environment of the coalface, the indexes of temperature, humidity, noise, illuminance, dust, harmful gas, and wind speed are selected to construct the environment evaluation index system, and the operating environment evaluation model of the coalface based on analytic hierarchy process (AHP) and matter-element theory (MET) is established. Firstly, the operation environment classification criterion is established; the environment objects, joint domain, and classical domain mater-element are built; and the correlation function is calculated. Secondly, the comprehensive correlation matrix is calculated and the environmental grade is judged. Finally, from the broad point of view, three measures are proposed to improve the operation environment of the coalface: development of the environmental evaluation index monitoring system, improvement on miners' safety awareness, and formulation of regulations and policies for coal mine operation environment. The research results can provide guidelines for miners, coal mining enterprises, and occupational environmental safety departments.